Higher Education Studies and Quality Assurance in African Universities - Kwandayi, Hardson (International Higher Education, 2021)
Quality assurance is an emerging area in higher education in Africa and its implementation could be enhanced through capacity building of institutional managers and quality assurance practitioners. One way of building capacity is through studying higher education as a discipline. Once managers understand major higher education concepts and theories, implementation of quality assurance systems is more likely to improve, thereby enhancing the quality of academic provision on the continent.